Penerapan Lean Software Development Method Dalam Merancang E-Scm Bahan Baku Banana Chips - Sa'adah, Nur; Kurniawan, Edi; M, Yori Apridonal (STMIK Royal Kisaran, 2025)
Abstract: In an increasingly competitive business era, information technology is key to managing data and information. E-SCM emerges as a strategic solution to integrate partners and manage inventory efficiently. This study focuses on the application of the Lean Software Development method to design an E-SCM system in the Banana Chips industry, which faces challenges in managing inventory and production processes. The main problems faced include the inability to manage raw material inventory and non-computerized records, resulting in inefficient use of time and costs. By applying Lean principles, such as eliminating unnecessary features, fast delivery, and team collaboration, the E-SCM Website is designed to be responsive to market needs and easy to understand by users. Before the E-SCM system is applied by users, developers test the system by measuring how well the system is understood by users. Before being implemented, the system was tested using the Usability Scale System (SUS) and prototype testing. The results of the questionnaire filled out by 5 respondents showed an average SUS score of 78, which was categorized as